Engaging Patients in the Veterans Health Administration's Lean Enterprise Transformation: A Qualitative Study. Issue 2 (6th April 2023) - Gray, Caroline P.; Azevedo, Kathryn J.; Urech, Tracy H.; Lerner, Barbara; Charns, Martin P.; Vashi, Anita A.
Abstract : Background and Objectives: Lean management is a strategy for improving health care experiences of patients. While best practices for engaging patients in quality improvement have solidified in recent years, few reports specifically address patient engagement in Lean activities. This study examines the benefits and challenges of incorporating patient engagement strategies into the Veterans Health Administration's (VA) Lean transformation. Methods: We conducted a multisite, mixed-methods evaluation of Lean deployment at 10 VA medical facilities, including 227 semistructured interviews with stakeholders, including patients. Results: Interviewees noted that a patient-engaged Lean approach is mutually beneficial to patients and health care employees. Benefits included understanding the veteran's point of view, uncovering inefficient aspects of care processes, improved employee participation in Lean events, increased transparency, and improved reputation for the organization. Challenges included a need for focused time and resources to optimize veteran participation, difficulty recruiting a diverse group of veteran stakeholders, and a lack of specific instructions to encourage meaningful participation of veterans. Conclusions/Implications: As the first study to focus on patient engagement in Lean transformation efforts at the VA, this study highlights ways to effectively partner with patients in Lean-based improvement efforts. Lessons learned may also help optimize patient input into quality improvement more generally.